2018
DOI: 10.1111/cen.13765
|View full text |Cite
|
Sign up to set email alerts
|

Impact of menopause on outcomes in prolactinomas after dopamine agonist treatment withdrawal

Abstract: Prolactin normalized over time in nearly half of the women and serum PRL 6-12 months after DA withdrawal is useful predictor. Nonetheless, 7% of the patients demonstrated adenoma regrowth which, given the life expectancy postmenopause, necessitate regular monitoring of the cases with persistent hyperprolactinaemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(39 citation statements)
references
References 23 publications
(30 reference statements)
0
35
0
4
Order By: Relevance
“…Based on current guidelines, patients with microprolactinoma who are asymptomatic or post-menopausal do not require treatment [25,82,90]. However, some authors advocate treatment in post-menopausal women due to the postulated negative effects of hyperprolactinaemia on bone health, weight gain, and insulin resistance [77,91].…”
Section: Conservative Managementmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on current guidelines, patients with microprolactinoma who are asymptomatic or post-menopausal do not require treatment [25,82,90]. However, some authors advocate treatment in post-menopausal women due to the postulated negative effects of hyperprolactinaemia on bone health, weight gain, and insulin resistance [77,91].…”
Section: Conservative Managementmentioning
confidence: 99%
“…However, some authors advocate treatment in post-menopausal women due to the postulated negative effects of hyperprolactinaemia on bone health, weight gain, and insulin resistance [77,91]. Post-menopausal women managed with a conservative strategy require ongoing surveillance for tumour progression [25,82,90].…”
Section: Conservative Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…Mallea-Gil et al followed 22 patients with microprolactinoma for a period between 4 and 192 months after CBG or bromocriptine suspension and found that only two patients needed to restart treatment for increasing PRL levels; among the remaining 20, a spontaneous reduction of PRL and a high rate of tumor disappearance at MRI were found [8]. In a recently published study from UK [9], Santharam et al found that among 16 postmenopausal women who stopped medical treatment after menopause with normalized prolactin levels, recurrence rate was significantly lower than that in premenopausal ones and comparable with that observed in our study, 31%. In their study, no difference in terms of recurrence rate was observed according to the adenoma size or drug used (bromocriptine vs. cabergoline).…”
Section: Discussionmentioning
confidence: 99%
“…Pathogenesis, natural history, and ideal treatment, in terms of duration or criteria for drug withdrawal, are not fully understood for this subtype of pituitary tumor. There is evidence that estrogens can stimulate normal and neoplastic lactotrophs' growth in vitro and in vivo animal models [4,5]; however, in humans, evidence is limited to a few studies which have shown a positive effect of the postmenopausal state on the course of disease, with spontaneous and progressive reduction of PRL and adenoma size observed in untreated women, and rare cases of hyperprolactinemia recurrence [6][7][8][9]. However, drawing definitive conclusions is difficult for these studies, because patients included were heterogeneous in regard to the etiology of hyperprolactinemia (microprolactinomas vs. macroprolactinomas vs. idiopathic hyperprolactinemia), to the previously employed treatment (surgery vs. medical treatment vs. no treatment) and to the specific drug administered (CBG vs. bromocriptine vs. other dopamine agonists).…”
Section: Introductionmentioning
confidence: 99%